Building the Character of Pancasila Students Through the Independent Curriculum - Ade Suherman; jamilah jamilah; Maskur Maskur; Odang Hermanto; Ana Maulana; Wandi Mulyana (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract Independent curriculum with diverse intracurricular learning where content will be optimized so that students have enough time to explore concepts and strengthen competencies. Teachers have the flexibility to choose various teaching tools so that learning can be adapted to the learning needs and interests of students. The dimensions of the Pancasila Student Profile are (1) Faith, fear of God Almighty, and noble character, (2) Global diversity, (3) Working together, (4) Independent, (5) Critical reasoning, and (6 ) Creative. The purpose of this service is to improve teacher competence regarding the character of Pancasila students through an independent curriculum. The subjects of service are Civics Education teachers, especially those in Malangbong District, Garut Regency through webinars and workshops. The results obtained from these activities are that teachers are motivated in understanding and developing the character of Pancasila students through an independent curriculum, besides that teachers can develop an independent curriculum in their respective schools. Abstrak Kurikulum Merdeka dengan pembelajaran intrakurikuler yang beragam di mana konten akan lebih optimal agar peserta didik memiliki cukup waktu untuk mendalami konsep dan menguatkan kompetensi. Guru memiliki keleluasaan untuk memilih berbagai perangkat ajar sehingga pembelajaran dapat disesuaikan dengan kebutuhan belajar dan minat peserta didik. Dimensi-dimensi Profil Pelajar Pancasila adalah (1) Beriman, bertakwa kepada Tuhan Yang Maha Esa, dan berakhlak mulia, (2) Berkebinekaan global, (3) Bergotong-royong, (4) Mandiri, (5) Bernalar kritis, dan (6) Kreatif. Tujuan pengabdian ini untuk meningkatkan kompetensi guru tentang karakter pelajar pancasila melalui kurikulum merdeka. Subjek pengabdian adalah guru-guru PKn khususnya yang berada di Kecamatan Malangbong Kabupaten Garut melalui kegiatan webinar dan workshop. Hasil yang diperoleh dari kegiatan tersebut yaitu termotivasi nya guru dalam memahami dan mengembangkan karakter pelajar pancasila melalui kurikulum merdeka, selain itu guru dapat mengembangkan kurikulum merdeka di sekolahnya masing-masing.